Crise contemporânea, microcrédito e trabalho informal: uma reflexão sobre a tendência desenvolvimentista da política social - Lima, Fabiana Alcântara (2015)
This Master thesis aims to analyze the displacement of the micro financial market for Social Policy, checking to what extent this strategy is developmental trend is founded on the hegemony of finance capital dominant debate.Trata this is to demonstrate the dual functionality of the integration microcredit social Policy in the discourse of coping with poverty and social inclusion. It appears that insofar as the financial market takes advantage of state and legal apparatus ideo-political discourse to legitimize the micro-credit as government policy, the state draws on the economic mechanisms promoted by major financial institutions to continue the dismantling of social rights of working class achieved after a long period of mobilization. And in this sense, the globalization of capital and the emergence of monetary policy play a crucial role for the capital return rates of profit lost with the collapse of the Golden Age. From the 1990s there is a new historical processuality envisioned, mainly from the restructuring of the productive capital and dissemination of artifacts from the flexible accumulation that spreads the benefits of working autonomously as the predominant form in contemporary capitalism. From the crisis that constitutes the hypertrophy of finance capital, microcredit has gained more centrality in the sphere of social policies. Not incidentally, worsen working conditions and incomes in the central and peripheral countries. In this regard, attention is diverted from the neoliberal offensive of the work for the emergency context of poverty, the debate that permeates the tendency neodesenvolvimentista Social Policy. In the survey of studies of the microcredit program, we found that this dynamic is expressed in its close relation to the informal labor, whose characteristics are contradictory and inconsistent with the proposal of offering monetary conditions to the lower classes. Thus, there is an attempt to resolve through political mechanisms, a problem situated in the capitalist structure and its form of organization, given that pauperism is a phenomenon inherent to this form of sociability. Finally, the dissertation seeks to demonstrate that it is within the capitalist society that the contradictions about development strategies are revealed more precisely.